Aquatic training in rehabilitation and preventive medicine - Prins, J. (Biomechanics and Medicine in Swimming XI, 2010)
Aquatic physical rehabilitation is now recognized and utilized as a "procedure," rather than a modality. The increased focus can be attributed in part to its evolution from the limited confines of"Hubbard Tanks," to the larger venues of swimming pools. The larger exercising areas serve as a venue for performing a greater variety of exercises, including those that require sustained propulsive movements. The physical properties of water provide a unique environment for improving strength, flexibility, and cardiovascular conditioning. Although exercise in the water, including formal swimming strokes have historically been used for the recovery from injury, there is now an increased focus on incorporating specific aquatic exercise protocols for treating persons with acute or chronic clinical conditions, including persons with permanent physical disabilities (Becker & Cole 1994; Cole et al. 2004; Genuario & Vegso 1990; LeFort 1994; Prins & Cutner 1999); Thein &Brody 1998).